THE PROBLEMATICS OF INDONESIAN EDUCATION IN A SOCIOLOGICAL PERSPECTIVE - Destiana Vidya Prastiwi; Inayatul Mardhiyah Indah Sulistiyani; Tutuk Ningsih (SOSIOEDUKASI, 2026)
Education is one of the main pillars in the development of a nation, as it plays a crucial role in improving the quality of human resources. However, in the context of Indonesia, the education system still faces various complex and multidimensional problems. These issues are not only related to academic aspects or educational policies, but are also influenced by various social, economic, and cultural factors that develop within society. This article aims to analyze the problems of education in Indonesia from the perspective of the sociology of education by examining various social factors that affect the quality of and access to education. This study employs a qualitative research method with a library research approach. The data collection technique used in this research is a literature study, which involves reading, reviewing, and analyzing various references, such as books on the sociology of education and collections of scientific journals related to educational problems in Indonesia from a sociological perspective. The results of the study indicate a significant disparity in access to and quality of education between urban and rural areas. In addition, family economic factors, social conditions of the community, and limitations in educational infrastructure also influence the success of the educational process. From a sociological perspective, education cannot be separated from the social dynamics that develop within society. Therefore, efforts to improve the quality of education in Indonesia require a comprehensive approach that takes into account various influencing social factors. This study is expected to contribute to a deeper understanding of educational issues and to serve as a basis for more inclusive and equitable educational policy-making.